Early predictors of oxaliplatin-induced cumulative neuropathy in colorectal cancer patients. Issue 4 (29th June 2013) - Velasco, Roser; Bruna, Jordi; Briani, Chiara; Argyriou, Andreas A; Cavaletti, Guido; Alberti, Paola; Frigeni, Barbara; Cacciavillani, Mario; Lonardi, Sara; Cortinovis, Diego; Cazzaniga, Marina; Santos, Cristina; et al.
Abstract : Objectives: Peripheral neuropathy ranks among the most common dose-limiting and disabling side-effect of oxaliplatin (OXA)-based chemotherapy. The aim of this prospective, multicentre study was to define early clinical and neurophysiological markers that may help to identify patients at risk of developing severe, treatment emergent, cumulative OXA-induced peripheral neuropathy (OXAIPN). Methods: 200 colorectal cancer patients, scheduled to receive OXA-based chemotherapy, were prospectively followed. Detailed neurological assessment employing the clinical Total Neuropathy Score (TNSc), oncological rating scales (National Common Institute-Common Toxicity Criteria V.3) and nerve conduction studies (NCS) were performed at baseline, mid-treatment and at the end of chemotherapy. Symptoms of OXA-induced acute neurotoxicity were systematically recorded. Results: According to TNSc, 36 (18%) patients developed grade 3 OXAIPN. These patients were predominantly men (p=0.005), presented a significant decrease in all NCS (p<0.001), reported more acute neuropathic symptoms (p<0.001) and received higher OXA cumulative dose (p=0.003). Multivariate analysis showed that three variables obtained at intermediate follow-up, namely, the number of acute symptoms (OR 1.9; CI 95% 1.2 to 3.2; p=0.012) and the >30% decrease in sensory nerve action potential amplitude from the baseline value in radial (OR 41.4; CI 95% 4.98 to 343.1; p=0.001) and dorsal sural nerves (OR 24.96; CI 95% 2.6 to 239.4; p=0.005) were independently associated with the risk of developing severe OXAIPN. Conclusions: High-grade OXA neurotoxicity can be predicted by clinical and neurophysiological information obtained at mid-treatment. Neurological assessment of acute neuropathy symptoms and radial and dorsal sural nerves NCS should be carefully monitored to predict and hopefully prevent the induction of severe OXAIPN.